2019
DOI: 10.1088/1742-6596/1254/1/012069
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of CNC (Computer Numerical Control) Based Automatic Stamp Batik Machine Program with Automatic Gripper Using Mach 3

Abstract: Batik is a painting or drawing on mori fabric that is made with canting tools. In Subsequent developments to speed up the process, stamp batik is used. CNC (Computer Numerical Control) based automatic stamp batik machine has been developed. This machine uses a manual batik stamper in the batik stamp (tool). The problem that arises in the use of manual chucking on this automatic stamp batik machine is the amount of time needed in the replacement and setting of the batik stamp. The design of a CNC based automati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Meski demikian, masih banyak masalah yang dihadapi oleh industri batik nasional, salah satunya adalah rendahnya regenerasi perajin batik tradisional terutama batik tulis [1]. Beberapa penelitian sudah dilakukan untuk mengatasi permasalahan tersebut, diantaranya adalah otomasi proses produksi menggunakan mesin Computer Numerical Control (CNC) untuk batik cap [2], [3], [4] dan batik tulis [1]. Berbagai penelitian juga telah dilakukan untuk mengoptimalkan proses produksi batik menggunakan mesin CNC, diantaranya adalah optimasi suhu dan feed rate [5], optimasi feed rate, jenis malam, dan ukuran nozzle [6], dan optimasi rute pembatikan menggunakan metaheuristik [7].…”
Section: Pendahuluanunclassified
“…Meski demikian, masih banyak masalah yang dihadapi oleh industri batik nasional, salah satunya adalah rendahnya regenerasi perajin batik tradisional terutama batik tulis [1]. Beberapa penelitian sudah dilakukan untuk mengatasi permasalahan tersebut, diantaranya adalah otomasi proses produksi menggunakan mesin Computer Numerical Control (CNC) untuk batik cap [2], [3], [4] dan batik tulis [1]. Berbagai penelitian juga telah dilakukan untuk mengoptimalkan proses produksi batik menggunakan mesin CNC, diantaranya adalah optimasi suhu dan feed rate [5], optimasi feed rate, jenis malam, dan ukuran nozzle [6], dan optimasi rute pembatikan menggunakan metaheuristik [7].…”
Section: Pendahuluanunclassified
“…Later in 1997, Elamvazuthi and Morris (1997) proposed an automatic batik coloring machine that consists of coloring software and controller subsystems. Dwinugroho et al (2019) had designed and developed an automatic batik stamp machine with grippers, based on the integration of CNC and programmable logic control (PLC). Their study revealed that the design can be stamped with higher consistency and accuracy compared to manual stamping.…”
Section: Batik Innovationsmentioning
confidence: 99%
“…Unfortunately, as with any craft-based industry that still uses traditional techniques, the number of batik workers is also seen to have dwindled in recent years (Khalili, 2018). Both nations find that it is getting harder to attract youths to participate in the local batik industry (Akhir et al, 2015; Dwinugroho et al, 2019; Khalili, 2018; Vatvani, 2019). The reasons for this scenario are attributed to various local economic factors as follows: low wages, decreasing product demand, unstable income, and the boom of other types of industries (Redzuan & Aref, 2011; Vatvani, 2019).…”
Section: Challenges In the Batik Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the integration of design and manufacturing with computer-based has been carried out [24], [25], [26]. Research of integration in batik production equipment by Ridho [27], Dwinugroho et al [28], Akhmad et al [29], Muthi'ah [30], Sudiarso and Kusumawardani [31], increase the ability to produce batik using a CNC batik. As a result, several processes in batik are done faster with a CNC.…”
Section: Introductionmentioning
confidence: 99%